Study of Air Flow in A Solar Collector Equipped with Two Inclined Obstacles - Benosman Fayssal (EDP Sciences, 2021)
In the present work we have studied the case of a conventional solar air collector and try to see how is it possible to improve it-s efficiency, by changing Reynolds number. Given the complexity of the problem we used the FLUENT calculation code. We made the mathematical model, then we gave a validation of our result by the results of Dimartini, we gave fields of speed, turbulence and a Nusselt profile and factor of friction as a function of the Reynolds Number. The results show that variation of Reynolds number has an influence on the performance of the solar collector, which is why we have used several values in order to observe the most suitable one.